Effects of combined use of thyme powder and aqueous extract on growth performance, carcass and organ characteristics, blood parameters, enzymes, immune system and jejunum morphology in broilers - Belali, M; Seidavi, A; Bouyeh, M (Journal of the Hellenic Veterinary Medical Society, 2022)
This experiment was performed to evaluate the effects of Thyme Extract (TE) and Thyme Powder (TP) on growth performance, carcass and organ characteristics, blood parameters, enzymes, immune system, and intestinal morphology in broilers. The experiment was performed based on a completely randomized design with 5 treatments, 4 replications and 10 Ross 308 male broilers in each replication for 42 days. Experimental treatments included aqueous extract of thyme (50 and 100 mg/kg feed) and thyme powder (150 and 250 mg/kg feed) which were used in combination with the basal diet (control). The effect of treatments was analyzed by SAS statistical software and the means were compared at 5% probability level with Duncan’s multiple range test. The results showed that in the final period of the experiment, different levels of TE and TP had a significant effect on daily weight gain, feed intake and conversion ratio improvement (P<0.05) so that the highest mean was related to treatment TE (100) + TP (250). The effects of different levels of TE and TP were significantly different on European index, economic value and total weight of the period (P<0.05), meaning that the highest means were related to TE (100) + TP (250), and the lowest means were related to TE (0) and TP (0). Different levels of TE and TP had significant effects on the relative weight of thymus, live weight, wing weight, ventricular fat and pancreas (P<0.05). The effect of different levels of TE and TP on the immunity was significant throughout the period (P<0.05). The higher levels of TE and TP increased the villi length, villi width, crypt depth, layer thickness and the ratio of villi length to crypt depth to the control treatment. Based on the results of the present study, the use of TE (100 mg/kg) + TP (250 mg/kg) in the diet is recommended to supplement the diet of Ross 308 broilers.